Adoptive Immunotherapy: Methods and Protocols - Ludewig, Burkhard; Hoffmann, Matthias W.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Over the last decade, major advances in our understanding of the immune system and its mechanisms have led to promising new treatment strategies. In Adoptive Immunotherapy: Methods and Protocols, leading experts describe in detail their optimal techniques for producing and characterizing the immunologically active cells and effector molecules now gaining wide use in the clinical treatment of patients. Taking advantage of the latest technologies, the authors present readily reproducible experimental protocols for the study of dendritic cells, T-cells, monoclonal antibodies, and bone marrow transplantation. The emphasis is on preclinicical and clinical applications and on the progress of selected approaches in clinical trials. Additional chapters cover the molecular definition of target antigens, mathematical modeling approaches to immonotherapy, and the utilization of regulatory T-cells. Theoretical overviews and discussion of future directions for the improvement of adoptive immunotherapy complete the volume. The protocols follow the successful Methods in Molecular Medicine$1!" (Bseries format, each offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and state-of-the-art, Adoptive Immunotherapy: Methods and Protocols offers an authoritative collection of novel techniques to study the adoptive transfer of tailored antigen-specific immune cells and to improve their clinical application.s
Exploiting Dendritic Cells for Active Immunotherapy of Cancer and Chronic Infection -- A Mathematical Approach for Optimizing Dendritic Cell-Based Immunotherapy -- Delivery of Tumor Antigens to Dendritic Cells Using Biodegradable Microspheres -- RNA Transfection of Dendritic Cells -- Isolation and Generation of Clinical-Grade Dendritic Cells Using the CliniMACS System -- Generation of Clinical-Grade Monocyte-Derived Dendritic Cells Using the CliniMACS System -- Adenoviral Transduction of Dendritic Cells -- Generation of Autologous Peptide- and Protein-Pulsed Dendritic Cells for Patient-Specific Immunotherapy -- Phenotypical and Functional Characterization of Clinical-Grade Dendritic Cells -- Dendritic Cells in Clinical Trials for Multiple Myeloma -- Identification of Tumor-Associated Autoantigens With SEREX -- Application of Proteomics and Protein Analysis for Biomarker and Target Finding for Immunotherapy -- Isolation and Expansion of Tumor-Reactive Cytotoxic T-Cell Clones for Adoptive Immunotherapy -- Tracking Adoptively Transferred Antigen-Specific T-Cells With Peptide/MHC Multimers -- Gene Transfer of MHC-Restricted Receptors -- Immunotherapy With CTL Restricted by Nonself MHC -- Designing TCR for Cancer Immunotherapy -- Isolation and Expansion of Tumor-Specific CD4+T-Cells by Means of Cytokine Secretion -- Methods for the Ex Vivo Characterization of Human CD8+T Subsets Based on Gene Expression and Replicative History Analysis -- Regulatory T-Cells in Antitumor Therapy Isolation and Functional Testing of CD4+CD25+Regulatory T-Cells -- Monoclonal Antibody-Based Strategies in Autoimmunity and Transplantation -- Producing Bispecific and Bifunctional Antibodies -- Antibody-Cytokine Fusion Proteins for the Therapy of Cancer -- Synthesis and Biological Evaluation of a Paclitaxel Immunoconjugate -- Cytotoxic Tumor Targeting With scFv Antibody-Modified Liposomes -- Intravenous Immunoglobulin Treatment for Fibrosis, Atherosclerosis, and Malignant Conditions -- Study of T-Cell Costimulatory Blockade In Vivo at a Single-Cell Level -- Stem Cell Transplantation: Graft-Mediated Antileukemia Effects -- Influence of Radiation Protocols on Graft-vs-Host Disease Incidence After Bone-Marrow Transplantation in Experimental Models -- Induction of Chimerism and Tolerance Using Freshly Purified or Cultured Hematopoietic Stem Cells in Nonmyeloablated Mice -- Induction of Mixed vs Full Chimerism to Potentiate GVL Effects After Bone-Marrow Transplantation -- Application of Donor Lymphocytes Expressing a Suicide Gene for Early GVL Induction and Later Control of GVH Reactions After Bone-Marrow Transplantation.
Keywords: Medicine; Immunology; Biomedicine; Immunology; Electronic books